2010
DOI: 10.1007/s00259-010-1437-x
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of hypoxia using [18F]HX4: a phase I trial

Abstract: Background and purpose Noninvasive PET imaging of tumour hypoxia could help in the selection of those patients who could benefit from chemotherapy or radiation with specific antihypoxic treatments such as bioreductive drugs or hypoxic radiosensitizers. In this phase I trial, we aimed to determine the toxicity of [ 18 F]HX4, a member of the 2-nitroimidazole family, at different dose levels. The secondary aim was to analyse image quality related to the HX4 dose and the timing of imaging. Methods Patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 9 publications
2
66
0
3
Order By: Relevance
“…Tracer synthesis of [ 18 F]HX4 was performed as described previously (14). [ 18 F]HX4 PET images were acquired and analyzed using a clinical PET/CT scanner (Siemens Biograph 40, Siemens Healthcare) as previously described (13).…”
Section: Pet Image Acquisition and Analysismentioning
confidence: 99%
“…Tracer synthesis of [ 18 F]HX4 was performed as described previously (14). [ 18 F]HX4 PET images were acquired and analyzed using a clinical PET/CT scanner (Siemens Biograph 40, Siemens Healthcare) as previously described (13).…”
Section: Pet Image Acquisition and Analysismentioning
confidence: 99%
“…An early clinical study using 18 F-fluoromisonidazole in a diverse range of tumor types found that, using this criterion to define hypoxia, 36 of 37 contained a measurable fractional hypoxic volume (2). An important caveat associated with these low tumor-to-blood ratios is that they are not entirely unexpected.…”
Section: Analysis Of Hypoxia Pet Imagesmentioning
confidence: 99%
“…These staining patterns suggest that individual PET voxels consist of far less than 100% hypoxic elements-typically 5%-30%. Thus, 18 F-fluoromisonidazole uptake within a hypoxic tumor voxel consisting of 20% hypoxia plus 80% normoxic tissue would not be expected to yield a ratio of 6:1 but only 2:1 (0.2 · 6 1 0.8 · 1 5 2.0). By comparison, the large uptake ratio between tumor and muscle seen with 18 F-FDG is a consequence of every tumor cell, rather than a fraction, exhibiting facilitated uptake and entrapment.…”
Section: Analysis Of Hypoxia Pet Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FAZA imaging provides similar hypoxia information to 18 F-FMISO, which may be helpful for therapy planning [96]. In addition, Lehtiö et al [97] [103,104]. Cu(II)-ATSM, a neutral lipophilic molecule, is another alternative PET probe for hypoxia imaging based on a metal complex of radioactive copper with ATSM, diacetylbis(N4-methylthiosemicarbazone), which is highly membrane permeable.…”
Section: Hypoxia Pet Imagingmentioning
confidence: 99%